Profiling bacterial communities and foodborne pathogens on food-associated surface following contact with raw beef, chicken and pork using 16s amplicon metagenomics - Emamjomeh, Mohsen; Mohd Hashim, Amalia; Abdul-Mutalib, Noor Azira; Khairil Mokhtar, Nur Fadhilah; Mustapha, Nurul Asyifah; Maeda, Toshinari; Amin-Nordin, Syafinaz (Elsevier, 2023)
Meat products are commonly associated with foodborne diseases outbreak. Bacteria have been long used as a hygienic indicator in the food industry. Food-contacted surfaces could be the source of contamination causing foodborne illness, particularly when involving raw meats. Hence, improving knowledge about bacteria that remains on meat-contacted surfaces can be influential in determining appropriate guidelines for food safety. This study aimed firstly to determine bacterial community structure and diversity. Secondly, to determine taxa cooccurrence network and differentially abundant bacteria and finally, to predict the functional profiles of bacterial communities residing on the food-associated surfaces used in industrial food preparation areas, i.e., aluminum tray, following contact with beef, chicken, and pork using 16S rRNA amplicon metagenomics on the Illumina MiSeq system. The most abundant bacteria on meat-contacted surfaces were determined, and Acinetobacter and Pseudomonas were among the dominant bacteria in all meat types. Chicken-contacted trays showed the highest species richness, followed by pork and beef, with a significant difference. The chicken-contacted tray bacterial community was significantly different from other groups. The co-occurrence network was predicted, and hub nodes were determined. Low- hub nodes were potential human pathogens or antibiotic-resistant. In addition, bacterial markers were determined; some were human pathogens, such as Shewanella in chicken, Staphylococcus in beef, and Klebsiella in pork. Although the predicted metagenomic functions were not significantly different, some were related to human diseases and resistance to antibiotics or disinfectants. In conclusion, bacterial pathogens were found on aluminum trays despite standard storage practices, demonstrating the need for proper hygiene instructions and regular cleaning of food preparation facilities and equipment to prevent cross-contamination. This study detailed bacterial taxa on meat-contacted trays, and the findings are critical to improving foodborne pathogen decontamination and developing safer food handling guidelines and standards. Radiation, heat, and chemical approaches are said to be influential in preventing contamination.